Short‐term Sahaja Yoga meditation training modulates brain structure and spontaneous activity in the executive control network. Issue 1 (28th November 2018) - Dodich, Alessandra; Zollo, Maurizio; Crespi, Chiara; Cappa, Stefano F.; Laureiro Martinez, Daniella; Falini, Andrea; Canessa, Nicola
Abstract: Introduction: While cross‐sectional studies have shown neural changes in long‐term meditators, they might be confounded by self‐selection and potential baseline differences between meditators and non meditators. Prospective longitudinal studies of the effects of meditation in naïve subjects are more conclusive with respect to causal inferences, but related evidence is so far limited. Methods: Here, we assessed the effects of a 4‐week Sahaja Yoga meditation training on gray matter density and spontaneous resting‐state brain activity in a group of 12 meditation‐naïve healthy adults. Results: Compared with 30 control subjects, the participants to meditation training showed increased gray matter density and changes in the coherence of intrinsic brain activity in two adjacent regions of the right inferior frontal gyrus encompassing the anterior component of the executive control network. Both these measures correlated with self‐reported well‐being scores in the meditation group. Conclusions: The significant impact of a brief meditation training on brain regions associated with attention, self‐control, and self‐awareness may reflect the engagement of cognitive control skills in searching for a state of mental silence, a distinctive feature of Sahaja Yoga meditation. The manifold implications of these findings involve both managerial and rehabilitative settings concerned with well‐being and emotional state in normal and pathological conditions. Abstract : We assessed the effects of a 4‐week Sahaja Yoga meditation training on gray matter volume and spontaneous resting‐state brain activity in a group of 12 meditation‐naïve healthy adults compared with 30 control subjects. The participants to meditation training showed increased gray matter density and a change in coherent brain activity in two adjacent regions of the right inferior frontal gyrus encompassing the anterior component of the executive control network. The significant impact of a brief meditation training on brain regions associated with self‐control and self‐awareness may reflect the engagement of cognitive control skills in searching for a state of mental silence, a distinctive feature of Sahaja Yoga meditation.